2015
DOI: 10.1002/jbm.b.33426
|View full text |Cite
|
Sign up to set email alerts
|

In vivobiological response to highly cross‐linked and vitamin e‐doped polyethylene—a particle‐Induced osteolysis animal study

Abstract: Polyethylene particle-induced osteolysis is the primary limitation in the long-term success of total joint replacement with conventional ultra high molecular weight polyethylene (UHMWPE). Highly cross-linked polyethylene (HXLPE) and vitamin E-doped cross-linked polyethylene (VE-HXLPE) have been developed to increase the wear resistance of joint surfaces. However, very few studies have reported on the incidence of particle-induced osteolysis for these novel materials. The aim of this study was to use a particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 38 publications
0
26
0
2
Order By: Relevance
“…In the present study, no significant differences in osteolysis were observed between the UHWMPE and VE-UHMWPE particle-treated mice, which is contradictory to the results reported by Bichara et al , who recently found a reduced osteolytic potential in VE-UHMWPE particle-treated mice compared to the controls (23). Another study on that topic published by Huang et al within this year also found similar signs of osteolysis between mice treated with vitamin E-containing particles and conventional UHMWPE wear particles (24). However, both studies investigated a murine calvaria model at a distinct time-point (10/14 days).…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, no significant differences in osteolysis were observed between the UHWMPE and VE-UHMWPE particle-treated mice, which is contradictory to the results reported by Bichara et al , who recently found a reduced osteolytic potential in VE-UHMWPE particle-treated mice compared to the controls (23). Another study on that topic published by Huang et al within this year also found similar signs of osteolysis between mice treated with vitamin E-containing particles and conventional UHMWPE wear particles (24). However, both studies investigated a murine calvaria model at a distinct time-point (10/14 days).…”
Section: Discussionmentioning
confidence: 71%
“…Using the same animal model a more recent study [ 48 ] investigated the biological response to participles debris of three commercially available UHMWPE: conventional UHMWPE, highly cross-linked UHMWPE (70 kGy) and VE-stabilized highly cross-linked UHMWPE (blended with 0.5% w/w, irradiated with a dose of 70 kGy). The same mass of wear debris (1 mg) was injected into the exposed calvaria area of animals.…”
Section: Resultsmentioning
confidence: 99%
“…There is strong evidence for the critical role of chronic low-grade inflammation in the mechanism of PPOL [7][8][9]. The evidence comes from in vitro studies [10][11][12][13][14], in vivo experiments [15][16][17][18][19], and analysis of tissues harvested during reoperations [20][21][22][23]. It has been repeatedly demonstrated in vitro and in vivo that after contact between artificially prepared prosthetic byproducts and immune cells, the latter express pro-inflammatory cytokines, chemokines and other substances ( Figure 1).…”
Section: The Case Of Inflammatory Osteolysismentioning
confidence: 99%